Data Envelopment Analysis for Measuring of Economic Growth in Terms of Welfare Beyond GDP - Martin Lábaj; Mikuláš Luptáčik; Eduard Nežinský (University of Economics in Bratislava, Department of Economic Policy, 2013)
Recent discussions on the definition of growth in terms of welfare beyond GDP suggest that it is of urgent need to develop new approaches for measuring the economic performance of the firms and national economies. The new concepts should take into account simultaneously economic as well as social and environmental goals. We first discuss several approaches to productivity measures. Then we extend the Data Envelopment Analysis models for environment to measure the so called eco-efficiency and for social indicators to take into account the social performance. For an illustration, we perform the analysis of 30 European countries in the year 2010. In the last section we discuss the possibilities of inter-temporal analysis of proposed models and of their use in ex-ante evaluation of different policy scenarios.
Keywords: C43; C61; O47; 330; eco-efficiency; data envelopment analysis; beyond GDP